2013
DOI: 10.1038/srep01839
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decoration of Au Nanoparticles on Monolayer MoS2 Single Crystals

Abstract: We report a controllable wet method for effective decoration of 2-dimensional (2D) molybdenum disulfide (MoS2) layers with Au nanoparticles (NPs). Au NPs can be selectively formed on the edge sites or defective sites of MoS2 layers. The Au-MoS2 nano-composites are formed by non-covalent bond. The size distribution, morphology and density of the metal nanoparticles can be tuned by changing the defect density in MoS2 layers. Field effect transistors were directly fabricated by placing ion gel gate dielectrics on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
217
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 395 publications
(241 citation statements)
references
References 48 publications
24
217
0
Order By: Relevance
“…The Raman A'1 peak of MoS2 blue-shifts and its intensity increases (relative to E'), thus indicating that MoS2 is less n-doped (or a decrease in the electron concentration). 44,45 The blue-shift of the WSe2 Raman A'1 peak implies that the WSe2 may become less p-doped (Supporting Figure S3 shows that in our separate experiment, p-doping from AuCl4 -causes a red-shift of Raman A'1 peak in monolayer WSe2). These phenomena suggest that the electrons transfer from MoS2 to WSe2, which is expected for the PN-junction composed by the p-type WSe2 and n-type MoS2.…”
Section: Resultsmentioning
confidence: 78%
“…The Raman A'1 peak of MoS2 blue-shifts and its intensity increases (relative to E'), thus indicating that MoS2 is less n-doped (or a decrease in the electron concentration). 44,45 The blue-shift of the WSe2 Raman A'1 peak implies that the WSe2 may become less p-doped (Supporting Figure S3 shows that in our separate experiment, p-doping from AuCl4 -causes a red-shift of Raman A'1 peak in monolayer WSe2). These phenomena suggest that the electrons transfer from MoS2 to WSe2, which is expected for the PN-junction composed by the p-type WSe2 and n-type MoS2.…”
Section: Resultsmentioning
confidence: 78%
“…2c. The Au nanoparticles are mainly concentrated along the edges of the sheet probably due to the higher reactivity of the edge defects 9 and aggregation of naked Au nanoparticles without a surfactant. Although various reducing agents have been proposed in the synthesis of metal nanoparticles, the use of 2D BP as the reductant has not been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4d shows Au4f5/2 and Au4f7/2 core level peaks at 88.2, 87.3, 84.3, and 83.5 eV, all of which are slightly shifted in comparison with bulk Au probably due to the Au-BP interaction. 9,47 Figure S5 depicts the Raman scattering spectrum of the BP@Au composites. Compared to the bare BP sheets, the BP@Au composites show a larger intensity ratio of the A 1 g to B 2g mode and red-shifts of the three prominent peaks ascribed to the Au-BP interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the functionalisation routes involving the addition of organic molecules, 20,21 it has been shown that CE-1T-TMDs react with AuCl 3 even in the absence of additional reducing agents. [25][26][27][28] As a result, Au 0 is produced and nucleates to form Au nanoparticles (AuNPs). Such TMD-Au hybrids are interesting for a number of applications ranging from rechargeable batteries, 27 to biosensing, 29,30 optoelectronics, [31][32][33] and catalysis.…”
Section: Introductionmentioning
confidence: 99%